2013
DOI: 10.1155/2013/350731
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Methane Potential of Agro Wastes

Abstract: The focus of our work is on anaerobic digestion of locally available agro wastes like coconut oil cake, cashew apple waste, and grass from lawn cuttings. The most productive agro waste, in terms of methane yield, was coconut oil cake and grass. The results showed that the initial volatile solids concentration significantly affected the biogas production. The methane yield from coconut oil cake was found to be 383 ml CH4/g VS and 277 ml CH4/g VS added at 4 and 4.5 g VS/l. In case of grass the biogas production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 24 publications
0
19
0
2
Order By: Relevance
“…COD for this ranges from 6000 to 90,000 mg/L [28]. Considering theoretical methane production of 0.35 L/g-of-COD [29], an average methane production of 0.03 Nm 3 /L of process water could be obtained which can supplement the energy needed for the hydrothermal process.…”
Section: Process Watermentioning
confidence: 99%
“…COD for this ranges from 6000 to 90,000 mg/L [28]. Considering theoretical methane production of 0.35 L/g-of-COD [29], an average methane production of 0.03 Nm 3 /L of process water could be obtained which can supplement the energy needed for the hydrothermal process.…”
Section: Process Watermentioning
confidence: 99%
“…These authors observed that the greatest biogas volume occurred with an HRT of 2 days, reaching a relative biogas production of 0.280 L CH4.g CODrem -1 . The theoretical biochemical methane potential per gram of CODrem is 0.350 L (Prabhudessai et al, 2013). However, some organic matter is used for growth of microorganisms and maintenance of cellular metabolism (Raposo et al, 2011).…”
Section: Effect Of Trh On Fermentation Of the Alkalinized Siementioning
confidence: 99%
“…However, the rate of biogas and methane productions differs significantly according to the operation of microwave pretreatment for decanter cake at various powers and heating times. The cumulative methane also increases with the increasing of the total amount of organic matter in a substrate after microwave pretreatment (Prabhudessai et al, 2013).…”
Section: Effect Of Power and Heating Time On Bmp Testmentioning
confidence: 94%
“…Total Volatile Solids (TVS) analysis determines the total amount of organic matter in the substrate. Thus, the increasing of TVS can enhance the organic biodegradability and the biogas and methane productions for anaerobic digestion (Prabhudessai et al, 2013). Microwave pretreatment has proved to be an effective way to break down the structure of fiber and lignocellulosic materials such as rice straw and switch grass (Zhu et al, 2006;Hu and Wen, 2008).…”
Section: Characteristics Of Decanter Cakementioning
confidence: 99%
See 1 more Smart Citation